Natural fluorescent carbon quantum dot and perovskite solar cell hole transport layer, active layer and electron transport layer thereof

By using natural fluorescent carbon quantum dots in perovskite solar cells, combining the active layer and electron transport layer of perovskite solar cells, the problem of insufficient application of carbon quantum dots in perovskite solar cells in the prior art is solved. , improves light utilization efficiency and stability, and achieves efficient light conversion and charge transmission.

CN119307257APending Publication Date: 2025-01-14ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411387098.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When existing perovskite solar cells combine carbon-based light-converting nanomaterials, there are few researches on the modification of carbon quantum dots to hole transport layer and electron transport layer, resulting in limited improvement in perovskite solar cells' performance, especially high There are few studies on the combination of quantum yield, nitrogen-doped carbon-based light-converting nanomaterials and the active layer of perovskite cell.

Method used

Natural fluorescent carbon quantum dots are prepared by raw materials such as rhodamine B, rhodamine 6G and PEG, combined with the active layer and electron transport layer of perovskite solar cells to form carbon quantum dots with high quantum yields, and through specific Process steps such as grinding, ultrasonic dispersion, solvothermal reaction and freeze-drying to obtain carbon quantum dot powders, which are integrated into the hole transport layer and electron transport layer of perovskite solar cells.

Benefits of technology

Improve the light utilization efficiency and weather resistance of perovskite solar cells, convert ultraviolet band light into visible light through the light conversion effect of carbon quantum dots, enhance the stability and conversion efficiency of the cell, and improve the carbon quantum dots with rich functional groups. The crystalline mass and interface structure of the active layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307257A_ABST
    Figure CN119307257A_ABST
Patent Text Reader

Abstract

The invention discloses a natural fluorescent-based carbon quantum dot and a perovskite solar cell hole transport layer, an active layer and an electron transport layer thereof, and the natural fluorescent-based carbon quantum dot is prepared by the following steps: weighing a proper amount of rhodamine B and rhodamine 6G, grinding and mixing uniformly in a mortar, dissolving in ammonia water, adding PEG, and stirring uniformly; carrying out ultrasonic dispersion until the solution is completely uniform, putting the solution into a high-temperature reaction kettle, and carrying out solvothermal reaction for 5-11 hours; adjusting the pH value of the liquid obtained by the reaction, centrifuging, carrying out suction filtration, removing solid particles, and carrying out ultrasonic treatment; and dialyzing the solution in a dialysis bag for 1-3 days, properly concentrating, and freeze-drying to obtain the product. The natural fluorescent carbon quantum dots have good conductivity, after a mesoporous structure is formed on the interface of the active layer and the electron transport layer in an auxiliary mode, the natural fluorescent carbon quantum dots and materials of the two layers jointly form a unique structure, the defects of the interface and the active layer are passivated on the premise that the charge transfer efficiency is not affected, and the performance and stability of the perovskite battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon-based new materials and solar cells, and in particular to natural fluorescent carbon quantum dots and a perovskite solar cell integrating the carbon quantum dots with a hole transport layer, an active layer and an electron transport layer. Background Art

[0002] Compared to other renewable energy sources, solar energy offers advantages such as small footprint, low cost, simplified maintenance, and a long service life. Years of development in the solar energy sector have resulted in the development of a variety of battery components, including crystalline silicon solar cells, thin-film cells, organic cells, and perovskite solar cells.

[0003] Perovskite solar cells are currently one of the most promising types of photovoltaic power generation. Unlike crystalline silicon solar cells, perovskite solar cells come in a wide variety of varieties, and the performance of cells produced using different materials and processes can vary significantly. Perovskite solar cells are primarily categorized by their raw materials into two types: all-inorganic and inorganic-organic hybrids. The former offers greater stability but relatively lower efficiency, while the latter boasts extremely high efficiency but suffers from limited weather resistance. After years of development, the power conversion efficiency of inorganic-organic hybrids has reached approximately 28%, approaching the theoretical single-cell efficiency limit of 33.7%. However, research into raw materials and synthesis processes is reaching a bottleneck, making breakthroughs extremely difficult. Improving the supporting components and auxiliary materials for perovskite solar cells offers a promising approach.

[0004] Photoconversion materials, such as fluorescent dyes, semiconductor quantum dots, and carbon-based nanomaterials, convert incident light of certain wavelengths into outgoing light of other wavelengths. Leveraging the photoconversion properties of these materials, solar cells can absorb spectral components of solar energy that were previously inaccessible. This increases the spectral absorption range of solar light, even extending it to encompass the entire spectrum, thereby improving the utilization rate of sunlight.

[0005] Carbon-based nanomaterials are one of the most promising photoconversion materials and have attracted widespread attention in the fields of new-generation semiconductor materials and functional materials. Carbon quantum dots, in particular, have attracted research and development from both industry and science due to their excellent photoconversion properties, non-toxic and environmentally friendly ecological properties, a wide range of precursor sources, and low preparation costs. The photoconversion capabilities of carbon quantum dots include upconversion (low energy converted to high energy) and downconversion (high energy converted to low energy). Upconversion is more difficult to achieve, generally absorbing infrared light to emit red light, and is often used in the medical field. Downconversion has a wider range of applications, mostly absorbing ultraviolet light to emit visible light. The wavelength of the emitted visible light can be adjusted by adjusting the synthetic raw materials and synthesis process of the carbon-based material.

[0006] Many studies have demonstrated the significant role of carbon quantum dots in the solar energy sector. The light that can be utilized by solar cells often only accounts for a small portion of solar radiation. For example, crystalline silicon solar cells mainly absorb red light, and most perovskite cells mainly absorb green light. The use of carbon quantum dots can convert some of the light that cannot be absorbed by the battery pack into light in the absorbable band. Currently, research on the use of light conversion materials in crystalline silicon solar cells is relatively mature, while research on the combination of perovskite solar cells and carbon-based light conversion materials is still relatively rare. Most of the research is direct coating for light conversion. The few studies that combine with cell structures mainly focus on improving the weather resistance of perovskite cells. In these studies, the improvement of the efficiency of perovskite solar cells by carbon quantum dots is not significant.

[0007] In fact, inorganic-organic hybrid perovskite solar cells have higher conversion efficiency because the central ions of their individual structures are often organic amine ion groups. The surface nitrogen-containing functional groups of some nitrogen-doped surface-functionalized carbon-based light-conversion nanomaterials are often in the form of amino groups, and the two have a certain surface compatibility. The light conversion ability of carbon-based light-conversion nanomaterials is generally directly linked to their quantum yield. The higher the quantum yield, the stronger the light conversion ability. Currently, the quantum yield of some green-emitting carbon-based light-conversion nanomaterials has reached 96%. However, there is currently little research on combining such high-quantum-yield, nitrogen-doped carbon-based light-conversion nanomaterials with the active layer of perovskite cells to improve the light utilization efficiency of perovskite solar cells. Research on the modification of hole transport layers (HTL) and electron transport layers (ETL) with carbon quantum dots is even scarcer, which greatly reduces new opportunities for improving the performance of perovskite solar cells. Summary of the Invention

[0008] To solve the above problems, the present invention provides a high quantum yield carbon quantum dot with natural fluorescent substance as the main raw material and a perovskite solar cell hole transport layer, active layer and electron transport layer integrating the carbon quantum dots.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A natural fluorescent carbon quantum dot is mainly prepared from the following raw materials in parts by weight:

[0011] 1-4 parts by weight of Rhodamine B, 0.5-1 parts by weight of Rhodamine 6G, and 30-50 parts by weight of PEG.

[0012] The preparation of the natural fluorescent carbon quantum dots of the present invention comprises the following steps:

[0013] S1. Weigh 1-4 parts by weight of Rhodamine B and 0.5-1 parts by weight of Rhodamine 6G, gently grind them in a mortar for 10-20 minutes, and mix them evenly to obtain a mixture;

[0014] S2, dissolving the mixture in ammonia water with a pH of 11-13, adding 30-50 parts by weight of PEG, and ultrasonically dispersing for 5-10 minutes to make the solution completely uniform;

[0015] S3. Place the completely uniform solution in a high-temperature reactor, perform a solvent thermal reaction at 150-210° C. for 5-11 hours, and adjust the pH value of the resulting liquid with dilute hydrochloric acid to be between 5 and 10;

[0016] S4, centrifuge the solution for 30-50 minutes, filter to remove solid particles, and sonicate for 0.5-1 hour;

[0017] S5. Place the solution in a dialysis bag and dialyze for 1-3 days. After appropriate concentration in a 50-70°C oven for 4-8 hours, freeze-dry for 16-36 hours to obtain a solid powder, which is the natural fluorescent carbon quantum dots.

[0018] The present invention also provides a perovskite solar cell active layer and electron transport layer, wherein the perovskite solar cell active layer and electron transport layer are doped with the above-mentioned natural fluorescent carbon quantum dots and are prepared from the following raw materials:

[0019] An ITO glass plate, 1.0-2.5 parts of PbI2 powder, 0.2-0.8 parts of CsI powder, 0.5-1.5 parts of PEG, 1-4.5 parts of SnO2 powder, 0.5-1 parts of TiO2 powder, 10-20 parts of DMF, and 80-120 parts of precursor liquid of the battery active layer doped with natural fluorescent carbon quantum dots.

[0020] Furthermore, the precursor liquid of the battery active layer is prepared from the following raw materials in parts by weight:

[0021] 85-100 parts of DMF, 15-30 parts of isopropyl alcohol, 3-5 parts of methylamine halide for perovskite cells, and 0.05-0.15 parts of the natural fluorescent carbon quantum dots.

[0022] Furthermore, the preparation of the active layer and the electron transport layer of the perovskite solar cell includes the following steps:

[0023] (1) After DMF and isopropanol are mixed, the methylamine halide for perovskite cells and the natural fluorescent carbon quantum dots are added to the mixture of DMF and isopropanol in small amounts and multiple times, and stirred appropriately during the period. After all are mixed, stirring is continued for 20-40 minutes, and ultrasonication is performed for 10-15 minutes to uniformly disperse the components. This mixed solution is the perovskite solar cell active layer precursor liquid integrated with natural fluorescent carbon quantum dots.

[0024] (2) Wetting SnO2 powder and TiO2 powder with 5-10 parts of pure water and stirring them uniformly, then adding PEG and stirring for 2-5 minutes, wherein the amount of pure water and PEG is distributed according to the weight ratio of the two powders; then, coating the obtained two powder slurries on the ITO glass plate in the order of TiO2 first and then SnO2, and drying them at room temperature for 20-40 minutes after coating. Repeat coating and drying 2-5 times to obtain an ITO glass plate with a SnO2 layer attached;

[0025] (3) Take 10-20 parts of DMF and mix them with PbI2 powder and CsI powder. Apply the mixture on the ITO glass plate with SnO2 layer attached by spin coating under nitrogen environment, keep it wet, and drip the precursor liquid of battery active layer. The flow rate of the precursor liquid of battery active layer is 20-50 μl / s. After the precursor liquid of battery active layer is dripped, they are rotated to dry and annealed in air. The interface between the active layer and the electron transport layer forms a mesoporous structure. Thus, the titanium ore solar cell active layer and its electron transport layer are prepared.

[0026] The present invention also provides a hole transport layer for a perovskite solar cell, which integrates the above-mentioned natural fluorescent carbon quantum dots and is prepared from the following raw materials in parts by weight:

[0027] 0.3 parts of 2,2',7,7'-tetrakis[n,n-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) powder, 3 parts of chlorobenzene, 5 parts of 4-tert-butylpyridine, 0.5 parts of lithium bis(trifluoromethanesulfonyl)imide powder, 5 parts of acetonitrile, 0.05-0.2 parts of the natural fluorescent carbon quantum dots, and 2-5 parts of isopropanol.

[0028] The present invention also provides a method for preparing the hole transport layer of the above-mentioned perovskite solar cell. During the preparation, the commonly used hole transport layer preparation method is referred to. First, after mixing chlorobenzene and 4-tert-butylpyridine, Spiro-OMeTAD powder is added to the mixed solution and stirred for 5-10 minutes to form a suspension; then, lithium bis(trifluoromethanesulfonyl)imide powder is added to acetonitrile to prepare the commonly used hole transport layer carrier. The natural fluorescent carbon quantum dots are then added to isopropanol to form a solution. Finally, the three solutions are mixed and fully stirred, and spin-coated onto the active layer under a nitrogen environment to form a hole transport layer integrating the natural fluorescent carbon quantum dots.

[0029] The present invention has the following beneficial effects:

[0030] 1) Utilizing the light conversion effect of carbon quantum dots, the ultraviolet light that cannot be used by perovskite solar cells is converted into green light that can be used by them. While reducing the degradation of perovskite solar cells caused by ultraviolet radiation, it also increases the total amount of light energy that can be used, while also improving its weather resistance and conversion efficiency.

[0031] 2) Using carbon quantum dots with specific functional groups as heterogeneous crystallization nuclei improves the crystallization quality of the perovskite active layer. The resulting perovskite crystal structure can be adjusted by adjusting the size distribution and average size of the embedded carbon-based light-conversion nanomaterials to maintain a cubic phase and improve its stability.

[0032] 3) The natural fluorescent-based carbon quantum dots of the present invention have good electrical conductivity. After assisting in forming a mesoporous structure at the interface between the active layer and the electron transport layer, they form a unique structure together with the materials of the two layers, passivating the defects of the interface and the active layer without affecting the charge transfer efficiency, thereby improving the performance and stability of the perovskite battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Other features, objects and advantages of the present invention will become more apparent upon reading the detailed description of non-limiting embodiments with reference to the following drawings:

[0034] Figure 1 This is a transmission electron microscope image of the natural fluorescent carbon quantum dots according to an embodiment of the present invention (the inset in the upper left corner shows the particle size distribution of the material).

[0035] Figure 2 Spectra of the natural fluorescent carbon quantum dots in the embodiment of the present invention.

[0036] Figure 3 This is a simplified diagram of the cross-sectional structure of a perovskite solar cell integrated with the natural fluorescent carbon quantum dots according to an embodiment of the present invention;

[0037] In the figure: 1-ITO glass plate, 2-electron transport layer, 3-interface mesoporous structure, 4-perovskite active layer, 5-hole transport layer, 6-gold electrode. DETAILED DESCRIPTION

[0038] The present invention will be described in detail below with reference to specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those skilled in the art, several variations and improvements can be made without departing from the scope of the present invention. These all fall within the scope of protection of the present invention.

[0039] In order to improve the performance and stability of perovskite batteries, the present invention provides natural fluorescent carbon quantum dots. The preparation of the natural fluorescent carbon quantum dots includes the following steps: weighing 2-5 parts by weight of rhodamine B and 0.5-1 part by weight of rhodamine 6G, gently grinding them in a mortar for 10-20 minutes, and uniformly mixing to obtain a mixture; dissolving the mixture in ammonia water with a pH of 11-13, adding 30-50 parts by weight of PEG, and ultrasonically dispersing for 5-10 minutes to make the solution completely uniform; placing the solution in a high-temperature reactor, performing a solvent thermal reaction at 150-210°C for 5-11 hours, and adjusting the pH value of the reaction liquid with dilute hydrochloric acid to be between 5 and 10; centrifuging the solution for 30-50 minutes, filtering to remove solid particles, and ultrasonicating for 0.5-1 hour; taking the solution and placing it in a dialysis bag, dialyzing it for 1-3 days, appropriately concentrating it in a 50-70°C oven, and freeze-drying it for 16-36 hours to obtain a solid powder, which is the natural fluorescent carbon quantum dots with high quantum yield.

[0040] In order to convert the ultraviolet band light that cannot be used by perovskite solar cells into green band light that can be used by them, while reducing the heat caused by ultraviolet radiation of perovskite solar cells, the present invention provides a perovskite solar cell integrated with the natural fluorescent carbon quantum dots, such as Figure 3 As shown, the perovskite solar cell adopts a high-transmittance mesoporous structure with a total of six layers, including, from bottom to top, an ITO glass plate 1, an electron transport layer 2, an interface mesoporous structure 3, a perovskite active layer 4, a hole transport layer 5, and a gold electrode 6;

[0041] in:

[0042] The thickness of the ITO glass plate 1 is 0.3 mm, which has extremely high conductivity and light transmittance, excellent mechanical strength and chemical stability, and is directly purchased; the thickness of the gold electrode 6 is 30 nm, which has extremely good conductivity and stability, and can be prepared by sedimentation method.

[0043] The electron transport layer 2 is prepared by coating, wherein the specific amount of each material is: 1.0-2.5 parts of PbI2 powder, 0.2-0.8 parts of CsI powder, 0.5-1.5 parts of PEG, 1-4.5 parts of SnO2 powder, 0.5-1 parts of TiO2 powder, and 10-20 parts of DMF; the perovskite active layer 4 is prepared by spin coating, wherein the specific amount of each material is: 85-100 parts of DMF, 15-30 parts of isopropyl alcohol, 3-5 parts of methylamine-type halide for perovskite cells, and 0.05-0.15 parts of natural fluorescent carbon quantum dot powder. The interfacial mesoporous structure layer 3 is a hybrid structure formed by the mutual penetration of the electron transport layer 2 and the perovskite active layer 4 under high-temperature activation. This structure can greatly increase the contact area between the electron transport layer 2 and the perovskite active layer 4, improving the electron transmission efficiency. Due to the increased disturbance caused by the introduction of carbon quantum dots during the formation of the mesoporous layer, the difficulty of forming the mesoporous structure is slightly reduced, and the degree of penetration of the two materials is increased, further improving the electron transmission efficiency. In addition, due to the auxiliary effect of carbon quantum dots on the crystallization of the perovskite active layer 4, the interfacial mesoporous layer 3 and the perovskite active layer 4 have fewer defects, which also improves the electron transmission efficiency and stability of the perovskite battery.

[0044] When preparing the electron transport layer 2, the interface mesoporous layer 3 and the perovskite active layer 4, first mix 85-100 parts of DMF and isopropanol, then add the methylamine halide and natural fluorescent carbon quantum dots for perovskite cells into the mixture of DMF and isopropanol in small amounts and multiple times, stirring appropriately during the process. After all are mixed, continue stirring for 20-40 minutes, and ultrasonicate for 10-15 minutes to evenly disperse the components. This mixture is the perovskite solar cell active layer precursor liquid integrated with natural fluorescent carbon quantum dots. Then, SnO2 powder and TiO2 powder are moistened and stirred with 5-10 parts of pure water respectively, and PEG is added and stirred for 2-5 minutes respectively, wherein the amount of pure water and PEG is distributed according to the weight ratio of the two powders; then, the obtained two powder slurries are coated on the ITO glass plate in the order of TiO2 first and SnO2 later, and dried at room temperature for 20-40 minutes after coating. The coating and drying are repeated 2-5 times to obtain an ITO glass with a SnO2 layer attached. Then, 10-20 parts of DMF is mixed with PbI2 powder and CsI powder. The mixture is applied to the ITO glass plate with the SnO2 layer using a spin coater under a nitrogen atmosphere. The plate is kept wet, and a precursor solution for the battery active layer is added dropwise at a flow rate of 20-50 μl / s. After the addition of the precursor solution, the active layer is spin-dried and annealed in air to form a mesoporous structure at the interface between the active layer and the electron transport layer. Thus, the titanium ore solar cell active layer, its electron transport layer, and the interfacial mesoporous structure layer are produced.

[0045] The hole transport layer 5 is a hole transport layer commonly used for modifying carbon quantum dots and is prepared by spin coating. The specific amounts of each material are: 0.3 parts of Spiro-OMeTAD powder, 3 parts of chlorobenzene, 5 parts of 4-tert-butylpyridine, 0.5 parts of lithium bis(trifluoromethanesulfonyl)imide powder, 5 parts of acetonitrile, 0.05-0.2 parts of the above-mentioned natural fluorescent carbon quantum dot powder, and 2-5 parts of isopropanol. During preparation, chlorobenzene and 4-tert-butylpyridine are first mixed, and then the Spiro-OMeTAD powder is added to the mixed solution and stirred for 5-10 minutes to form a suspension; then the lithium bis(trifluoromethanesulfonyl)imide powder is added to acetonitrile to obtain a hole transport layer carrier solution; then the natural fluorescent carbon quantum dots are added to isopropanol to form a solution; finally, the three solutions are mixed and stirred thoroughly, and then spin-coated onto the active layer under a nitrogen environment to form a hole transport layer integrating the natural fluorescent carbon quantum dots. The hole transport layer integrated with natural fluorescent carbon quantum dots can convert light mainly in the range of 300-400nm into green light of around 500nm. While reducing ultraviolet light exposure and improving the stability of inorganic-organic perovskite solar cells, it increases the total amount of available light it receives and improves its conversion efficiency.

[0046] The naturally fluorescent, high-quantum-yield carbon quantum dots of the embodiments of the present invention provide extremely high photoluminescence efficiency, thereby ensuring light conversion capability. When the carbon quantum dots are integrated into the electron transport layer of a perovskite solar cell, the light conversion capability of the carbon quantum dots effectively utilizes ultraviolet light in solar radiation that is harmful to the perovskite solar cell, converting it into usable green light, thereby improving the stability and energy conversion efficiency of the perovskite solar cell and effectively solving the stability problem of inorganic-organic hybrid perovskite solar cells. When integrated into the active layer and hole transport layer of the perovskite solar cell, due to the rich surface functional groups of the carbon quantum dots, the active layer will produce fewer defects when generating perovskite crystals due to the passivation effect of the carbon quantum dots. The participation of the carbon quantum dots in the interface mesoporous layer also reduces the difficulty of preparing the mesoporous structure, and its dispersion effect is more uniform and stable, thereby improving the stability and conversion efficiency of the perovskite solar cell.

[0047] Example 1

[0048] A perovskite solar cell integrated with natural fluorescent carbon quantum dots, comprising an ITO glass plate, a perovskite solar cell active layer and an electron transport layer integrated with natural fluorescent carbon quantum dots, an interface mesoporous structure formed by mutual penetration of the electron transport layer and the perovskite active layer under high-temperature excitation, a perovskite solar cell hole transport layer integrated with natural fluorescent carbon quantum dots, and a gold electrode;

[0049] Prepared by the following steps:

[0050] First, prepare natural fluorescent carbon quantum dots: weigh 2 parts by weight of rhodamine B and 0.5 parts by weight of rhodamine 6G, gently grind them in a mortar for 15 minutes, and mix them evenly to obtain a mixture; dissolve the mixture in ammonia water with a pH of 11, add 35 parts by weight of PEG, and ultrasonically disperse for 10 minutes to make the solution completely uniform; place the solution in a high-temperature reactor, and perform solvent thermal reaction at 165°C for 9 hours, and adjust the pH value of the reaction liquid to 8 with dilute hydrochloric acid; centrifuge the solution for 30 minutes, filter it to remove solid particles, and ultrasonicate it for 0.5 hours; take the solution and place it in a dialysis bag, dialyze it for 2 days, appropriately concentrate it in a 50°C oven, and freeze-dry it for 24 hours to obtain the product.

[0051] Secondly, prepare the active layer and electron transport layer of perovskite solar cells integrated with natural fluorescent carbon quantum dots:

[0052] Weigh by weight: 90 parts of DMF, 20 parts of isopropyl alcohol, 3.5 parts of methylamine halide for perovskite cells, 0.05 parts of carbon quantum dot powder, 1.5 parts of PbI2 powder, 0.5 parts of CsI powder, 0.5 parts of PEG, 2.0 parts of SnO2 powder, and 0.6 parts of TiO2 powder;

[0053] The perovskite cell methylamine halide and natural fluorescent carbon quantum dot powder were added to 80 parts of DMF in small amounts and multiple times with appropriate stirring. After the mixture was fully mixed, stirring was continued for 25 minutes and ultrasonication was performed for 10 minutes to evenly disperse the components. This mixture was the precursor liquid for the active layer of the perovskite solar cell. The SnO2 powder and TiO2 powder were moistened with 10 parts of pure water, respectively, and each was stirred evenly. PEG was added and stirring was continued for 2 minutes. The amount of pure water and PEG was distributed according to the weight ratio of the two powders. They were then coated on an ITO glass plate in sequence. After coating, the plates were dried at room temperature for 20 minutes. The coating and drying were repeated three times to obtain an ITO glass plate with a SnO2 layer. 10 parts of DMF were then mixed with PbI2 and CsI. The mixture was then coated on the ITO glass plate with the SnO2 layer prepared above using a spin coater under a nitrogen environment. Keep them moist, drip the perovskite solar cell active layer precursor liquid at a flow rate of 40μl / s, and finally spin dry them and anneal them in air to form a mesoporous structure at the interface between the active layer and the electron transport layer.

[0054] Then, a hole transport layer for perovskite solar cells integrated with natural fluorescent carbon quantum dots was prepared.

[0055] Weigh by weight: 0.3 parts of Spiro-OMeTAD powder, 3 parts of chlorobenzene, 5 parts of 4-tert-butylpyridine, 0.5 parts of lithium bis(trifluoromethanesulfonyl)imide) powder, 5 parts of acetonitrile, 0.05 parts of natural fluorescent carbon quantum dots, and 2 parts of isopropanol;

[0056] After mixing chlorobenzene and 4-tert-butylpyridine, Spiro-OMeTAD powder is added to the mixed solution and stirred for 5-10 minutes to form a suspension; then lithium bis(trifluoromethanesulfonyl)imide powder is added to acetonitrile to obtain a hole transport layer carrier solution; then the natural fluorescent carbon quantum dots are added to isopropanol to form a solution; finally, the three solutions are mixed and fully stirred, and spin-coated onto the active layer under a nitrogen environment to form a hole transport layer integrating the natural fluorescent carbon quantum dots;

[0057] Finally, gold electrodes are prepared on the prepared titanite solar cell active hole transport layer using gold deposition, and the obtained finished product is the perovskite solar cell with the integrated natural fluorescent carbon quantum dots.

[0058] Example 2

[0059] A perovskite solar cell integrated with natural fluorescent carbon quantum dots differs from Example 1 in that: the raw material ratios of the perovskite active layer 4 precursor liquid and the hole transport layer 5, wherein the perovskite active layer 4 precursor liquid comprises the following raw materials in parts by weight: 90 parts of DMF, 20 parts of isopropyl alcohol, 3.0 parts of methylamine-type halide for perovskite cells, and 0.1 part of the above-mentioned natural fluorescent carbon quantum dot powder; the hole transport layer comprises the following raw materials in parts by weight: 0.2 parts of 5Spiro-OMeTAD powder, 1.4 parts of chlorobenzene, 1.0 parts of 4-tert-butylpyridine, 0.5 parts of lithium bis(trifluoromethanesulfonyl)imide powder, 3.0 parts of acetonitrile, 0.1 parts of the above-mentioned natural fluorescent carbon quantum dot powder, and 1.5 parts of isopropyl alcohol.

[0060] Comparative Example 1

[0061] The perovskite solar cell differs from Example 1 in that the natural fluorescent carbon quantum dot powder is not added when preparing the electron transport layer 2, the perovskite active layer 4 precursor liquid, and the hole transport layer. Instead, they are replaced by a mixed solution of DMF and isopropanol in equal parts by weight (mixed in a ratio of 8:2 by weight), and a conventional perovskite solar cell is prepared according to the preparation process.

[0062] The perovskite solar cells obtained in Example 1, Example 2, and Comparative Example 1 were integrated into a 19 mm × 19 mm perovskite solar cell group, and their power conversion efficiency (PCE) was tested under the same conditions. The test results are as follows:

[0063] Table 1 Power conversion efficiency (PCE)

[0064] Test performance Example 1 Example 2 Comparative Example 1 PCE 25.61% 25.85% 24.26%

[0065] As can be seen from Table 1 above, in the present invention, the power conversion efficiency of the perovskite solar cell obtained by the present invention is significantly improved through the participation of carbon quantum dots, and the power of the perovskite solar cell can be adjusted to a certain extent by adjusting the content of carbon quantum dots.

[0066] Furthermore, the three groups of perovskite solar cells were placed in a high-humidity environment and the PCE of each group was tested after a period of time to compare their weather resistance. The results showed that the inclusion of naturally fluorescent carbon quantum dots can improve the weather resistance and stability of perovskite solar cells to a certain extent, but the degree of doping is not necessarily better. Observations have found that after the concentration of carbon quantum dots reaches a certain level, the PCE of the perovskite solar cell is greatly improved, but the stability is slightly reduced. Therefore, when doping, it is necessary to select an optimal dosage that takes into account both power conversion efficiency and weather resistance.

[0067] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various variations or modifications within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A natural fluorescent carbon quantum dot, characterized in that: It is mainly prepared from the following raw materials in parts by weight: Rhodamine B 1-4 parts by weight, Rhodamine 6G 0.5-1 parts by weight, PEG 30-50 parts by weight.

2. The natural fluorescent carbon quantum dots according to claim 1, characterized in that: The preparation comprises the following steps: S1, weighing 1-4 parts by weight of rhodamine B and 0.5-1 parts by weight of rhodamine 6G, grinding them in a mortar for 10-20 minutes, and mixing them evenly to obtain a mixture; S2, dissolving the mixture in ammonia water with a pH of 11-13, adding 30-50 parts by weight of PEG, and ultrasonically dispersing for 5-10 minutes to make the solution completely uniform; S3, placing the completely uniform solution in a high-temperature reaction kettle, and after solvent thermal reaction at 150-210°C for 5-11 hours, adjusting the pH value of the liquid obtained by the reaction to between 5-10 with dilute hydrochloric acid; S4, centrifuge the solution for 30-50 minutes, filter to remove solid particles, and ultrasonicate for 0.5-1 hour; S5. Place the solution in a dialysis bag and dialyze for 1-3 days. Concentrate in a 50-70°C oven for 4-8 hours and freeze-dry for 16-36 hours to obtain a solid powder, which is the natural fluorescent carbon quantum dots.

3. A perovskite solar cell active layer and electron transport layer, characterized in that: The solar cell active layer and the electron transport layer are doped with the natural fluorescent carbon quantum dots described in claim 2.

4. The perovskite solar cell active layer and electron transport layer according to claim 3, characterized in that: The solar cell active layer and the electron transport layer are prepared from the following raw materials: An ITO glass plate, 1.0-2.5 parts of PbI2 powder, 0.2-0.8 parts of CsI powder, 0.5-1.5 parts of PEG, 1-4.5 parts of SnO2 powder, 0.5-1 parts of TiO2 powder, 10-20 parts of DMF, and 80-120 parts of precursor liquid of a battery active layer doped with the natural fluorescent carbon quantum dots.

5. The perovskite solar cell active layer and electron transport layer according to claim 4, characterized in that: The precursor liquid of the battery active layer doped with the natural fluorescent carbon quantum dots is prepared from the following raw materials in parts by weight: 85-100 parts of DMF, 15-30 parts of isopropanol, 3-5 parts of methylamine type halide for perovskite battery, and 0.05-0.15 parts of the natural fluorescent carbon quantum dots.

6. The perovskite solar cell active layer and electron transport layer according to claim 5, characterized in that: The preparation comprises the following steps: (1) After DMF and isopropanol are mixed, methylamine halide for perovskite battery and natural fluorescent carbon quantum dots are added to the mixture of DMF and isopropanol in small amounts and multiple times, and stirred appropriately during the process. After all the mixture is mixed, stirring is continued for 20-40 minutes, and ultrasonication is performed for 10-15 minutes to make the components evenly dispersed, thereby obtaining a precursor solution of the battery active layer; (2) Wetting SnO2 powder and TiO2 powder respectively with 5-10 parts of pure water and stirring them evenly, then adding PEG and stirring for 2-5 minutes, wherein the amount of pure water and PEG is distributed according to the weight ratio of the two powders; then, coating the obtained two powder slurries on the ITO glass plate in the order of TiO2 first and then SnO2, and drying them at room temperature for 20-40 minutes after coating, repeating the coating and drying 2-5 times to obtain an ITO glass plate with a SnO2 layer attached; (3) Take 10-20 parts of DMF and mix them with PbI2 powder and CsI powder. Use a spin coater to apply the mixture on the ITO glass plate with the SnO2 layer attached to it in a nitrogen environment, keep it wet, and drip the precursor liquid of the battery active layer. The flow rate of the precursor liquid of the battery active layer is 20-50 μl / s. After the precursor liquid of the battery active layer is dripped, it is rotated to dry and annealed in air. The interface between the active layer and the electron transport layer forms a mesoporous structure.

7. A hole transport layer for a perovskite solar cell, characterized in that: The battery hole transport layer integrates the natural fluorescent carbon quantum dots described in claim 2.

8. The hole transport layer of a perovskite solar cell according to claim 7, characterized in that: The battery hole transport layer is prepared from the following raw materials in parts by weight: 0.3 parts of 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) powder, 3 parts of chlorobenzene, 5 parts of 4-tert-butylpyridine, 0.5 parts of lithium bis(trifluoromethanesulfonyl)imide powder, 5 parts of acetonitrile, 0.05-0.2 parts of the natural fluorescent carbon quantum dots, and 2-5 parts of isopropanol.

9. The hole transport layer of a perovskite solar cell according to claim 8, characterized in that: During the preparation, first, chlorobenzene and 4-tert-butylpyridine are mixed, and Spiro-OMeTAD powder is added to the mixed solution and stirred for 5-10 minutes to form a suspension; then, lithium bis(trifluoromethanesulfonyl)imide powder is added to acetonitrile to obtain a hole transport layer carrier solution; then, the natural fluorescent carbon quantum dots are added to isopropanol to form a solution; finally, the three solutions are mixed and fully stirred, and spin-coated onto the active layer in a nitrogen environment to form a hole transport layer integrating the natural fluorescent carbon quantum dots.